Thermal Performances and Fluidity of Biodegradable Poly(L-lactic acid) Filled with N, N'-Oxalyl Bis(piperonylic acid) Dihydrazide as a Nucleating Agent - Lisha ZHAO; Yanhua CAI (Medžiagotyra, 2021)
N, N'-oxalyl bis(piperonylic acid) dihydrazide (PAOD) was obtained through the amination of piperonylic acid chloride and its structure was characterized by Fourier transform infrared spectrometer and nuclear magnetic resonance. Melting blend technology was used to prepare the modified poly(L-lactic acid) (PLLA) containing the various loading PAOD as a new organic nucleating agent. The thermal performances including crystallization, melting behavior and thermal decomposition process, as well as the fluidity of PAOD-nucleated PLLA were investigated via a series of tests. The DSC results showed that, in comparison to DSC curve of the virgin PLLA, the DSC curves of all PLLA/PAOD appeared the sharp melt-crystallization peak, and a higher PAOD concentration caused the melt-crystallization to occur in the higher temperature region and reduced the negative effect of the high cooling rate on the melt-crystallization process. However, with increasing of PAOD concentration, the cold-crystallization enthalpy decreased from 24.4 J/g to 16.7 J/g. The melting peak after melt-crystallization depended on the heating rate and the PAOD concentration; and the double melting peaks appeared after isothermal crystallization in low temperature region was thought to be due to the melting-recrystallization. The addition of PAOD decreased the onset decomposition temperature of PLLA, but the onset decomposition temperature was determined by the PAOD concentration and the intermolecular interaction of PLLA and PAOD. Additionally, the PAOD could considerably improve the fluidity of PLLA.